Sensing-Based Interaction for Information Navigation on Handheld Displays - Michael Rohs; Georg Essl (Advances in Human-Computer Interaction)
Information navigation on handheld displays is characterized by the small display dimensions and limited input capabilities of today’s mobile devices. Special strategies are required to help users navigate to off-screen content and develop awareness of spatial layouts despite the small display. Yet, handheld devices offer interaction possibilities that desktop computers do not. Handheld devices can easily be moved in space and used as a movable window into a large virtual workspace. We investigate different information navigation methods for small-scale handheld displays using a range of sensor technologies for spatial tracking. We compare user performance in an abstract map navigation task and discuss the tradeoffs of the different sensor and visualization techniques.